Foliar nutrient contents of tropical tree species under different management and climate conditions - Estrada-Medina, Hector; Ferrer, Miriam M.; Montañez-Escalante, Patricia; Pech-Puch, Grelty; Álvarez-Rivera, Oscar O. (Ecosistemas y Recursos Agropecuarios, 2023)
Plant species, regional conditions and management practices haveeffects on plant nutrient uptake; however, its study is complex as their effects occur all at the same time. This study compares the foliar nutrient contents of Brosimum alicastrum (evergreen), Cordia dodecandra (deciduous), and Spondias purpurea (deciduous) tree individuals growing in homegardens and forest at two climate regions. 20 individuals per species and their associated soils were sampled.  Soil pH, electrical conductivity, sand, silt, and clay percentages, as well as edaphic and foliar C, N, P, K, Na, and Ca contents were analyzed. Nutrient levels in soils associated with each species were significantly different (λ Wilks = 0.61, F12,372 = 8.70; p < 0.0001). Forest soils had higher contents of C and N; homegarden soils had higher pH, and more silt and phosphorus. The foliar nutrient contents of the three species were significantly different (λ Wilks = 0.11, F12,458 = 77.71; P < 0.0001). B. alicastrum had greater contents of Na and K; C. dodecandra had more Ca, and S. purpurea had higher levels of N and P. Foliar P content was three times higher in homegarden trees than in forest individuals. Our results suggest that management primarily determines foliar P content; C and N levels depend  on species and region; and both, the species and management determine K, Na, and Ca contents.
Keywords: Brosimum alicastrum Sw.; Cordia dodecandra DC.; Spondias purpurea L.; Evergreen and deciduous trees; Homegardens; Tropical forests